IDENTIFICATION IDENTIFICATION OF THE CHEMICAL COMPOUNDS OF CITRUS HYSTRIX ESSENTIAL OIL, CANANGA ORDORATA ESSENTIAL OIL, AND POGOSTEMON CABLIN BENTH ESSENTIAL OIL USING GAS CHROMATOGRAPHY-MASS SPECTROPHOTOMETRY (GC-MS) - Yelfi Anwar; Efa Bonita; Andrianopsyah Mas Jaya Putra (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Essential oils, commonly known as etheric oils (essential oil, volatile oil), are produced by plants and can be obtained from the roots, stems, leaves, and flowers of plants. This study aims to determine the chemical components of kaffir lime (Citrus hystix) essential oil, ylang ylang (Cananga ordorata), and patchouli oil (Pogostemon cablin benth) obtained from farmers and refiners in Lembang, West Java. The composition of this essential oil was analyzed using the gas chromatography–mass spectrometry (GC–MS) method. The results of the analysis of the chemical components of the essential oil constituents of kaffir lime showed that the main components included linalyl acetate (20.59%), D-limonene (17.77%), and linalool (15.19%). In ylang-ylang oil, bioactive compounds such as sesquiterpenes, namely caryophyllene, were found in as much as 14.36%, which has anti-inflammatory, anti-bacterial, and local anesthetic properties. Identification of patchouli oil with its main component, namely patchouli alcohol, at 19.27%.